Versatile roles of polyamines in improving abiotic stress tolerance of plants - Shao, Jinhua; Huang, Kai; Batool, Maria; Idrees, Fahad; Afzal, Rabail; Haroon, Muhammad; Noushahi, Hamza Armghan; Wu, Weixiong; Hu, Qiliang; Lu, Xingda; Huang, Guoqin; Aamer, Muhammad; et al. (Frontiers in Plant Science, 2022)
In recent years, extreme events of environmental cues such as abiotic stresses including, frequent droughts with irregular precipitation, salinity, metal contamination and temperature fluctuations, are escalating the damage to plant’s optimal productivity worldwide. Therefore, the yield maintenance under extreme events needs improvement in multiple mechanisms that can minimize the influence of abiotic stresses. Polyamines (PAs) are pivotally needful for defensive purpose under adverse abiotic conditions, but their molecular interplay in this remains speculative. The PAs accretion is one of the most notable metabolic responses of plants under stress challenges. The recent studies reported the beneficial roles of PAs in plant development including metabolic and physiological processes unveiled their potential for inducing tolerance against adverse conditions. This review presented an overview of research about the most illustrious and remarkable achievements strengthening plant tolerance to drought, salt and temperature stresses by exogenous application of PAs. We also summarized the knowledge related to underlying processes associated with stress tolerance and PAs signaling pathways. We focus on up-to-date evidences regarding metabolic and physiological role of PAs with exogenous applications that provide protection to plants under unfavorable climatic conditions. Conclusively, the literature proposed that PAs impart an imperative role in abiotic stress tolerance in plants. This implies potential important feedback of PAs and plant’s stress tolerance under unfavorable cues.